Cookgenix.AI: Sistem Rekomendasi Resep Masakan Berbasis Bahan dan Preferensi Pengguna Menggunakan Metode Collaborative Filtering dan FP-Growt - Sarwendra Sarwendra; Krisna Pujanthi; Reva Audia Manurung; Mulyadi Mulyadi (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
The development of artificial intelligence (AI) technology has driven innovation in various sectors, including the culinary industry. This study develops Cookgenix.AI, an intelligent chatbot that provides recipe recommendations based on available ingredients and user preferences. This system implements two main methods, namely Collaborative Filtering to understand user preference patterns and FP-Growth to extract associations between ingredients. The evaluation results show that the system is able to provide accurate and relevant recommendations, with a precision of 87% and a recall of 85%. Cookgenix.AI is expected to be a practical solution in efficient and personalized daily menu planning. Keywords: chatbot, recommendation system, recipe, collaborative filtering, FP-Growth, artificial intelligence.